Late Development of FcεRγneg Adaptive Natural Killer Cells Upon Human Cytomegalovirus Reactivation in Umbilical Cord Blood Transplantation Recipients - Muccio, Letizia; Falco, Michela; Bertaina, Alice; Locatelli, Franco; Frassoni, Francesco; Sivori, Simona; Moretta, Lorenzo; Moretta, Alessandro; Della Chiesa, Mariella (Frontiers in Immunology, 2018)
In human NK cells, HCMV has been shown to be a driving force capable of inducing the expansion of a highly differentiated NKG2C+CD57+ subset, persisting over time in both HCMV+ healthy subjects and UCBT recipients experiencing HCMV viral reactivation. In HCMV+ healthy subjects, such expanded NK-cells are characterized by epigenetic modifications that modulate their phenotypic and functional characteristics. In particular, an enhanced ADCC activity is detectable in NK cells lacking the signaling protein FcεRγ. Timing and mechanisms involved in the acquisition of HCMV-induced, adaptive-like features by NK cells are currently unknown. In this study, we investigated the de-novo acquisition of several adaptive features in NK cells developing after UCBT by monitoring NK-cell differentiation for at least two years after transplant. In UCBT recipients experiencing HCMV reactivation, a rapid phenotypic reconfiguration occurred resulting in the expected expansion of CD56dim NKG2C+CD57+ NK cells. However, while certain HCMV-driven adaptive hallmarks, including high KIR, LILRB1, CD2 and low/negative NKG2A, Siglec-7, and CD161 expression, were acquired early after UCBT (namely by month 6), downregulation of the signaling protein FcεRγ was detected at a later time interval (i.e. by month 12). This feature characterized only a minor fraction of the HCMV-imprinted NKG2C+CD57+ CD56dim NK cell subset, while it was detectable in higher proportions of CD57+ NK cells lacking NKG2C. Interestingly, in patients developing a hyporesponsive CD56-CD16bright NK-cell subset, FcεRγ downregulation occurred in these cells earlier than in CD56dim NK cells. Our data suggest that the acquisition of a fully “adaptive” profile requires signals that may lack in UCBT recipients and/or longer time is needed to obtain a stable epigenetic reprogramming. On the other hand, we found that both HCMV-induced FcεRγneg and FcεRγ+ NK cells from these patients, display similar CD107a degranulation and IFN-γ production capabilities in response to different stimuli, thus indicating that the acquisition of specialized effector functions can be achieved before the “adaptation” to HCMV is completed. Our study provides new insights in the process leading to the generation of different adaptive NK-cell subsets and may contribute to develop new approaches for their employment as novel immunotherapeutic tools.